2015
DOI: 10.1177/1098612x15589878
|View full text |Cite
|
Sign up to set email alerts
|

Cytauxzoonosis in cats

Abstract: Cats with outdoor access in endemic areas should receive effective tick treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…has recently been described [25], but subclinical infection was highly prevalent in another epidemiological study [23]. Cytauxzoon felis infection has been described to frequently cause anemia in the domestic cat [21, 44, 45] and Criado-Fornelio et al [22] described the presence of low haematocrit and haemoglobin values in a Spanish Cytauxzoon sp.-infected cat that also showed an increased level of glucose, hepatic enzymes and serum albumin. Only one of the Cytauxzoon sp.-infected cat in our study that had haematological and biochemical results showed slight normocytic, normochromic anemia, lymphopenia, thrombocytopenia and hyperproteinemia.…”
Section: Discussionmentioning
confidence: 99%
“…has recently been described [25], but subclinical infection was highly prevalent in another epidemiological study [23]. Cytauxzoon felis infection has been described to frequently cause anemia in the domestic cat [21, 44, 45] and Criado-Fornelio et al [22] described the presence of low haematocrit and haemoglobin values in a Spanish Cytauxzoon sp.-infected cat that also showed an increased level of glucose, hepatic enzymes and serum albumin. Only one of the Cytauxzoon sp.-infected cat in our study that had haematological and biochemical results showed slight normocytic, normochromic anemia, lymphopenia, thrombocytopenia and hyperproteinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Cytauxzoonosis due to C. felis is characterized by an acute febrile illness with profound fever (although hypothermia may be identified in moribund cats), depression and vocalization (so-called death yowl). Laboratory abnormalities at the time of presentation are more marked and include frequent thrombocytopenia and neutropenia as well as non-regenerative anemia, leukopenia, hyperbilirubinemia and bilirubinuria, mild elevations in liver enzymes, hyperglycemia and hypoalbuminemia [2, 3]. Interestingly, the Portuguese case was evocative of the American disease.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive and critical treatment is a mainstay of therapy for American cytauxzoonosis [2, 3, 20]. Clinical recovery is not rapid with most patients getting worse during the first 24-48 h followed by a gradual improvement over the next several days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatozoon species are parasites from the phylum of Apicomplexa with a definitive host (a blood-sucking invertebrate) and an intermediate host (a vertebrate) (1-3). There are more than 340 species of Hepatozoon and about 46 of them infect mammals (2,3). Despite a few differences in the ecology and biology of these protozoa, the primary route of Hepatozoon species transmission to the vertebrate hosts is represented by the ingestion of the invertebrate host carry-ing mature oocysts (1,4).…”
Section: Introductionmentioning
confidence: 99%